(untitled) - Tyson, Shaun (London, 1997)
Human resource Management: Linking Strategy to Practice provides students with both an understanding of traditional human resource concepts and a framework for making decisions about when specific practices can be most beneficial to an organization. this link between strategy and practice is necessary for students to be able to learn how to correctly apply human resource tools to improve organizations
Keywords: Personnel management,Strategic planning